Analysis Of The Popularity Of Dubai Chocolate Among Generation Z In Ciracas, East Jakarta - Claudya Chrisli; Ni Ketut Veri Kusumaningrum; Ni Nyoman Widani (Politeknik Internasional Bali, 2025)
This research explores the growing popularity of Dubai Chocolate among Generation Z in Ciracas, East Jakarta, driven by social media trends and influencer marketing. Dubai Chocolate, known for its premium taste featuring the pistachio and knafeh fillings, has become a viral sensation, especially on social media platforms such as TikTok and Instagram. This study employs a descriptive qualitative method, utilizing likert-scale questionnaires and in-depth interviews with both consumers and local business owners involved in selling the product. The AIDA model comprising Attention, Interest, Desire, and Action is used as the analytical framework to understand consumer behavior and the factors influencing purchasing decisions. The results show that social media virality, aesthetic packaging, exclusivity, and positive reviews from food influencers significantly contribute to consumer interest and brand recognition. Moreover, the hype around Dubai Chocolate has influenced local culinary trends, encouraging small food businesses to create innovative dessert products inspired by the original. The research provides insight into how food trends can shape market behavior and offers valuable references for culinary entrepreneurs and marketers targeting Gen Z consumers.